Matrix Metalloproteinase-9 Mediates RSV Infection in Vitro and in Vivo - Kong, Michele Y.F. (Viruses, 2015)
Respiratory Syncytial Virus (RSV) is an important human pathogen associated with substantial morbidity and mortality. The present study tested the hypothesis that RSV infection would increase matrix metalloproteinase (MMP)-9 expression, and that MMP-9 inhibition would decrease RSV replication both in vitro and in vivo. RSV A2 infection of human bronchial epithelial cells increased MMP-9 mRNA and protein release. Cells transfected with siRNA against MMP-9 following RSV infection had lower viral titers. In RSV infected wild-type (WT) mice, MMP-9, airway resistance and viral load peaked at day 2 post infection, and remained elevated on days 4 and 7. RSV infected MMP-9 knockout (KO) mice had decreased lung inflammation. On days 2 and 4 post inoculation, the RSV burden was lower in the MMP-9 KO mice compared to WT controls. In conclusion, our studies demonstrate that RSV infection is a potent stimulus of MMP-9 expression both in vitro and in vivo. Reduction of MMP-9 (via siRNA knockdown, and in MMP-9 KO mice) resulted in decreased viral replication. Our findings suggest MMP-9 is a potential therapeutic target for RSV disease.